Psychological and biochemical strain in firemen`s work. - Kalimo, Raija; Lehtonen, Anne; Daleva, Meglena; Kuorinka, Ilkka (Scandinavian Journal of Work, Environment & Health, 1980)
Mental load and strain in the work of firemen and fire alarm center operators were studied in a group of 260 fireman and 6 female full-time operators from three fire brigades. The firemen proved to be satisfied with their work, and signs of chronic psychological problems were uncommon. Situational work load and related strain may, however, be extreme during active operations. A large proportion (42%) of the firemen suffered from strain after the 24-h long daily work period. Those who had recently worked as paramedics in the ambulance service or in the alarm center were under more strain than ordinary fire fighters. Biochemical stress indicators revealed a high activation of firemen at the alarm center. The difference found between firemen and full-time female operators may be due to a variation in the adaptive functions of the two sexes.
Keywords: alarm center; ambulance paramedic; biochemical strain; fireman; firemen`s work; job satisfaction; mental strain; psychological strain; psychophysiological stress